2015
DOI: 10.1177/0954008315577822
|View full text |Cite
|
Sign up to set email alerts
|

Control of morphology and electromagnetic properties of polypyrrole synthesized by the template method

Abstract: This article presents a contribution to a better understanding of the effects of pH value on the morphology, conductivity, and reflection loss of polypyrrole (PPy) prepared at different pH values using indigo carmine (IC) as the synthesis template. The results indicate that the morphology of PPy changes from spiral rods to nonspiral rods, then to particles, which is attributed to the gradual morphological change of IC micelle templates from prismatic structure to rugby-like structure, and finally to spherical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In this regard, dispersions of PPy nanoparticles can be used in molecular electronics and microelectronic circuits whereas nanosized particles lead to better processability of PPy. A variety of methods to produce ICP nanomaterials have been reported such as in situ chemical oxidative polymerization, electrochemical polymerization, templates, electrospinning, interfacial polymerization, self‐assembly, seeding growth, oligomer‐assisted polymerization, and emulsion polymerization . Among these approaches, emulsion polymerization technique has attracted considerable interest due to its procedure simplicity .…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, dispersions of PPy nanoparticles can be used in molecular electronics and microelectronic circuits whereas nanosized particles lead to better processability of PPy. A variety of methods to produce ICP nanomaterials have been reported such as in situ chemical oxidative polymerization, electrochemical polymerization, templates, electrospinning, interfacial polymerization, self‐assembly, seeding growth, oligomer‐assisted polymerization, and emulsion polymerization . Among these approaches, emulsion polymerization technique has attracted considerable interest due to its procedure simplicity .…”
Section: Introductionmentioning
confidence: 99%
“…Polyaniline (PANI), polypyrrole (PPy), polyindole (PIN), and polythiophene (PT) are important class of conducting polymers. 1 4 Among them, an interesting choice to the conducting polymer is PPy due to its unchallenging mode of synthesis (when compared with PANI, PIN, and PT), slender weight, and enormous biocompatibility as well as environmental stability. 5,6 However, the deficiency of the mechanical, electrical, and thermal stabilities makes PPy unhandy for many industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, insoluble complex templates with lamellar mesostructures were formed with a noble metal compound and a cationic surfactant such as CTAB [70]. Other surfactants that have been investigated include indigo carmine [71] and Pluronic ® F127 [72].…”
Section: Recent Advances In the Synthesis Of Cp Nanomaterialsmentioning
confidence: 99%
“…In addition, insoluble complex templates with lamellar mesostructures were formed with a noble metal compound and a cationic surfactant such as CTAB [70]. Other surfactants that have been investigated include indigo carmine [71] and Pluronic ® F127 [72]. As a possible milestone for industrial fabrication of colloidal crystal templates, Choi et al [61] demonstrated an efficient method to fabricate large-area two-dimensional (2D) colloidal crystals as a template for nanopatterning of CPs; this method involves the electrophoretic deposition of negatively charged polystyrene colloidal particles and the assembly of the colloidal particles to 2D colloidal crystals at the air-water interface.…”
Section: Recent Advances In the Synthesis Of Cp Nanomaterialsmentioning
confidence: 99%